LAMA PEMAKAIAN KONTRASEPSI SUNTIK DEPO MEDROKSIPROGESTERON ASETAT DENGAN KADAR KOLESTEROL PADA AKSEPTOR KB - Ni Made Werdianti Prawerti; Nengah Runiari; I Dewa Made Ruspawan (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2019)
This study aims to the relationship between duration of DMPA injection useage with cholesterole levels on family planning acceptors in South Denpasar I Primary Health Center on 2019. The type of research used is non-experimental with the type of correlational withapproach cross sectional. Sampling uses non probability sampling with a purposive sampling technique of 35 respondents. The instrument of collection through interviews and examination of cholesterol levels was measured by the Electrode-Based Biosensor method using the EasyTouch GCU Kit. The results showed that the majority of DMPA injection contraceptive use for ≥36 months (57.1%), most had rather high cholesterol levels (40.0%). The hypothesis test used is Chi-Square test with a p value = 0,000 (α = 0.05), so that there is the relationship between duration of DMPA injection useage with cholesterole levels on family planning acceptors in South Denpasar I Primary Health Center on 2019.